Community mental health in Malaysia: marriage of psychiatry and public health - Jamaiyah H. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2000)
﻿Mental Health Services in Malaysia has long been confined to psychiatry whose history in this country dated back as early as 1827. However, aspects of prevention of mental disorders and promotion of mental health had lagged behind. The public health burden of mental health problems and disorders now is too high for this to continue. Thus the need for a more comprehensive outlook of mental health services in the country to redress these issues. This paper attempts to give an insight into the matter. It starts with a discussion on the underlying concepts involved. This is followed by a brief review of the different models of mental health services and an in depth discussion on the model adopted by Malaysia under the new Community Mental Health Programme. An update as per the current status of the programme is given followed by a discussion on the what are our strength and weaknesses, threats and opportunities. To conclude the paper some recommendations are suggested as the way forward for the success of the Community Mental Health Programme in Malaysia.